2020
DOI: 10.1038/s41598-020-71445-5
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emission computed tomography (SPECT) or positron emission tomography (PET) imaging for radiotherapy planning in patients with lung cancer: a meta-analysis

Abstract: Functional imaging modalities enable practitioners to identify functional lung regions. This analysis evaluated the feasibility of nuclear medicine imaging to avoid doses to the functional lung in radiotherapy (RT) planning for patients with lung cancer. This systematic review and meta-analysis was carried out according to PRISMA-P guidelines. A search of EMBASE and PubMed for studies published throughout the last 20 years was performed using the following search criteria: (a) ‘lung cancer’ or ‘lung malignancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This is somewhat countered by the higher concentration that may be achieved in tiny clusters of cells as compared to large, quantifiable tumours. Different techniques can be used to obtain data on the distribution of radiopharmaceuticals in a patient, which include single-photon emission computed tomography (SPECT) and positron emission tomography (PET) [ 92 ], as well as whole-body emission counting [ 93 ] and planar γ-imaging [ 94 ]. Several dosimetry methods have been methodically and rigorously researched and developed.…”
Section: Radiopharmaceuticals With Radiolabelled Peptides Towards Can...mentioning
confidence: 99%
“…This is somewhat countered by the higher concentration that may be achieved in tiny clusters of cells as compared to large, quantifiable tumours. Different techniques can be used to obtain data on the distribution of radiopharmaceuticals in a patient, which include single-photon emission computed tomography (SPECT) and positron emission tomography (PET) [ 92 ], as well as whole-body emission counting [ 93 ] and planar γ-imaging [ 94 ]. Several dosimetry methods have been methodically and rigorously researched and developed.…”
Section: Radiopharmaceuticals With Radiolabelled Peptides Towards Can...mentioning
confidence: 99%
“…However, these parameters are evaluated across the whole lung volume and do not account for functional differences between lung regions. Recently, regional lung functionality assessment has been shown to enable highly functional lung areas to be spared from irradiation and thus can be used to design treatment plans that reduce the risk of injury ( Hoover et al, 2014 ; Bucknell et al, 2018 ; Lee and Park, 2020 ; Vinogradskiy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The field of functional imaging of the lung is underrapid development in recent years. Single-photon emission computed tomography (SPECT) imaging is traditionally used to provide functional information of the lung including ventilation using technetium-99 mor xenon-133 and perfusion using technetium-99 m. 10 Early work by Marks et al 11 demonstrated that pulmonary perfusion indicated by SPECT showed unique values in "designing radiation portals to minimize irradiation of functioning lung". More interestingly, pulmonary perfusion was noticed to decline in 1-6 months in areas receiving 40 Gy of dose.…”
Section: Introductionmentioning
confidence: 99%